THE ROLE OF MARKETING KNOWLEDGE ENGINEERING IN IMPROVING CUSTOMER RESPONSE: AN ANALYTICAL STUDY OF THE OPINIONS OF A SAMPLE OF PHARMACISTS IN AL-DIWANIYAH GOVERNORATE - Estabraq Ali Kareem; Ameera Ghasi Ajel; Fatima Tawfiq Jaber (Scholars Digest Publishing, 2026)
This research aims to identify the role of marketing knowledge engineering, across its dimensions (multiple types of marketing knowledge, multiple types of marketing experience, multiple methods of representing marketing knowledge, and multiple methods of using marketing knowledge), in improving customer response across its dimensions (word-of-mouth/verbal advertising, and customer intent to convert) among a sample of pharmacists in Al-Diwaniyah Governorate. The research sample consisted of 165 pharmacists. The descriptive analytical method was used to achieve the research objectives and develop its instruments, using the statistical software programs AMOS version 29 and SPSS version 29. The results showed that pharmacists' reliance on marketing knowledge systems and principles helps in identifying patients' needs and preferences more accurately, enabling the provision of more specialized and higher-quality services, and contributing to enhanced customer satisfaction and response.
Keywords: Marketing knowledge engineering, customer response.